ANTI-INFLAMMATORY ACTIVITY OF NGHE BO CAP (CURCUMA RANGJUED) RHIZOME EXTRACT AND MOLECULAR DOCKING ANALYSIS OF ITS MAJOR BIOACTIVE COMPOUNDS (Tạp chí Y học Cộng đồng, 2026)
"Nghe bo cap" is the local name for a plant characterized by yellow, scorpion-shaped rhizomes. Taxonomic identification classified this species as Curcuma rangjued (Hue et al., 2024), distributed primarily in mountainous regions of Dak Glong Commune, Dak Glong District, Lam Dong Province, Vietnam. Traditional medicine practitioners have employed herbal preparations from this species to treat bronchitis, asthma, gastric disorders, and infections, attributing these applications to purported anti-inflammatory properties. However, no scientific evidence has substantiated these medicinal claims.This study extracted essential oil from C. rangjued rhizomes and evaluated its inhibitory effects on pro-inflammatory mediators (TNF-α and PGE-2) through in vitro assays. Molecular docking analysis investigated the mechanisms of action for key bioactive compounds identified in the essential oil and assessed potential anti-inflammatory activities.The essential oil of C. rangjued (GEC) inhibited TNF-α expression at 11.38 μM (p < 0.05) and PGE-2 expression at 22.36 μM (p < 0.01). Molecular docking revealed that germacrone and curcumenol exhibited binding affinities toward PGE-2 of 0.96 μM and 0.2 μM, respectively, and toward TNF-α of 1.39 μM and 0.10 μM, respectively. These compounds formed stable interactions with TNF-α, consistent with the observed anti-inflammatory activity. These findings suggest that C. rangjued rhizome possesses therapeutic potential for anti-inflammatory  through the bioactive compounds germacrone and curcumenol. Further in vivo studies are warranted to validate these preliminary results and establish clinical applications.
Keywords: Curcuma rangjued, Cytokine, Inflammation, Nghe Bo Cap, TNF-α, PGE-2